Hydration Effects on Energy Relaxation of Ferric Cytochrome C Films after Soret-Band Photoexcitation - Ye, S. J.; Markelz, A. (Journal of Physical Chemistry B, 2010)
Protein hydration plays a critical role in protein dynamics and biological processes. Pump-probe transmission measurement has been applied to investigate the hydration effects on the energy relaxation of a heme protein ferric Cytochrome c (Cyt c) film after soret-band photoexcitation. Transient dynamics study indicates that the energy internal conversion time of similar to 300 fs is independent of hydration. The vibrationally excited electronic ground-state recovery rates show two transitions at the hydration level of h = 12.4-16.5% and 21.7-23.5%. The first transition occurs at the hydration level for the onset of an increasing ferric Cyt c flexibility while the second transition occurs at the saturated hydration level. The hydration dependence of steady-state electronic absorption spectrum results shows that the Q-band peak is nearly constant in center wavelength, but the line width surprisingly narrows with increasing hydration. For the similar to 695 nm absorbance associated with the MET80-Fe bond, the intensity increases with increasing hydration and slightly blue shifts. The 695 nm peak grows rapidly at h = 12.4% and then plateaus at h = 21.7%. This research shows that similar to 695 nm absorbance and ground-state recovery rates are sensitive to the hydration of the protein. This study will aid in understanding how hydration modulates the activity of the protein dynamics at a local level.
ISI Document Delivery No.: 681CT Times Cited: 3 Cited Reference Count: 87 Cited References: Bagchi B, 2005, CHEM REV, V105, P3197, DOI 10.1021/cr020661+ BAI YW, 1995, SCIENCE, V269, P192, DOI 10.1126/science.7618079 Bertini I, 2000, J MAGN RESON, V147, P1, DOI 10.1006/jmre.2000.2131 Bizzarri AR, 2002, J PHYS CHEM B, V106, P6617, DOI 10.1021/jp020100m BONE S, 1985, J MOL BIOL, V181, P323, DOI 10.1016/0022-2836(85)90096-8 Bone S, 2008, J PHYS CHEM B, V112, P10071, DOI 10.1021/jp8009782 BULL HB, 1968, ARCH BIOCHEM BIOPHYS, V128, P488, DOI 10.1016/0003-9861(68)90055-6 BULL HB, 1970, ARCH BIOCHEM BIOPHYS, V137, P299, DOI 10.1016/0003-9861(70)90443-1 CHAMPION PM, 1981, J CHEM PHYS, V75, P490, DOI 10.1063/1.441846 Chen EF, 1999, J AM CHEM SOC, V121, P3811, DOI 10.1021/ja983169+ Chen JY, 2005, PHYS REV E, V72, DOI 10.1103/PhysRevE.72.040901 Cianetti S, 2004, J AM CHEM SOC, V126, P13932, DOI 10.1021/ja046442i Dragomir I, 2007, BIOPHYS J, V92, P989, DOI 10.1529/biophysj.106.095976 Eaton W A, 1981, Methods Enzymol, V76, P175 EATON WA, 1967, J CHEM PHYS, V46, P2533, DOI 10.1063/1.1841081 EATON WA, 1968, J CHEM PHYS, V49, P985, DOI 10.1063/1.1670263 Ehrler OT, 2009, ACCOUNTS CHEM RES, V42, P769, DOI 10.1021/ar800263z FERRAND M, 1993, P NATL ACAD SCI USA, V90, P9668, DOI 10.1073/pnas.90.20.9668 GASCOYNE PRC, 1977, J CHEM SOC FARAD T 1, V73, P171, DOI 10.1039/f19777300171 GIBSON QH, 1957, NATURE, V180, P1416, DOI 10.1038/1801416b0 Gregory R.B., 1995, PROTEIN SOLVENT INTE HALLE B, 1981, J AM CHEM SOC, V103, P500, DOI 10.1021/ja00393a004 Halle B, 2004, PHILOS T R SOC B, V359, P1207, DOI 10.1098/rstb.2004.1499 Henchman RH, 2002, PROTEIN SCI, V11, P2080, DOI 10.1110/ps.0214002 Hertel IV, 2006, REP PROG PHYS, V69, P1897, DOI 10.1088/0034-4885/69/6/R06 Jayaram B, 2004, ANNU REV BIOPH BIOM, V33, P343, DOI 10.1146/annurev.biophys.33.110502.140414 Jimenez R, 2002, J PHYS CHEM B, V106, P9172, DOI 10.1021/jp0209648 JONES CM, 1993, P NATL ACAD SCI USA, V90, P11860, DOI 10.1073/pnas.90.24.11860 Joti Y, 2008, BIOPHYS J, V94, P4435, DOI 10.1529/biophysj.107.118042 Jougeward K. A., 1988, J BIOL CHEM, V263, P6027 Kamal JKA, 2004, P NATL ACAD SCI USA, V101, P13411, DOI 10.1073/pnas.0405724101 Kamei T, 2002, BIOPHYS J, V82, P418, DOI 10.1016/S0006-3495(02)75406-4 Kholodenko Y, 2000, CHEM PHYS, V259, P71, DOI 10.1016/S0301-0104(00)00182-8 Kubinec M. G., 1992, CURR OPIN STRUC BIOL, V2, P828 Kumar ATN, 2001, J PHYS CHEM B, V105, P7847, DOI 10.1021/jp0101209 Levy Y, 2004, P NATL ACAD SCI USA, V101, P3325, DOI 10.1073/pnas.0400157101 Levy Y, 2006, ANNU REV BIOPH BIOM, V35, P389, DOI 10.1146/annurev.biophys.35.040405.102134 LI P, 1992, J CHEM PHYS, V97, P3214, DOI 10.1063/1.463008 Lim MH, 1996, J PHYS CHEM-US, V100, P12043, DOI 10.1021/jp9536458 Lowenich D, 2008, PHOTOCHEM PHOTOBIOL, V84, P193, DOI 10.1111/j.1751-1097.2007.00219.x Makinen M. W., 1983, IRON PORPHYRINS, P41 Manas ES, 1999, J PHYS CHEM B, V103, P6334, DOI 10.1021/jp9908552 MARGOLIASH E., 1966, ADVANCE PROTEIN CHEM, V21, P113, DOI 10.1016/S0065-3233(08)60128-X MARTIN JL, 1994, METHOD ENZYMOL, V232, P416 MARTIN JL, 1992, ANNU REV BIOPH BIOM, V21, P199, DOI 10.1146/annurev.biophys.21.1.199 MARTIN JL, 1983, P NATL ACAD SCI-BIOL, V80, P173, DOI 10.1073/pnas.80.1.173 Mitra RK, 2007, LANGMUIR, V23, P10224, DOI 10.1021/la7014447 MOORE GR, 1990, CYTOCHROMES EVOLUTIO Negrerie M, 2006, J PHYS CHEM B, V110, P12766, DOI 10.1021/jp0559377 Nibbering ETJ, 2005, ANNU REV PHYS CHEM, V56, P337, DOI 10.1146/annurev.physchem.56.092503.141314 Oleinikova A, 2007, BIOPHYS J, V93, P2986, DOI 10.1529/biophysj.107.108753 OTTING G, 1989, J AM CHEM SOC, V111, P1871, DOI 10.1021/ja00187a050 Pal SK, 2004, CHEM REV, V104, P2099, DOI 10.1021/cr020689l Pascher T, 1996, SCIENCE, V271, P1558, DOI 10.1126/science.271.5255.1558 Qiu WH, 2006, P NATL ACAD SCI USA, V103, P13979, DOI 10.1073/pnas.0606235103 Qiu WH, 2005, J PHYS CHEM B, V109, P16901, DOI 10.1021/jp0511754 Raschke TM, 2006, CURR OPIN STRUC BIOL, V16, P152, DOI 10.1016/j.sbi.2006.03.002 Reddy CK, 2001, J MOL BIOL, V314, P619, DOI 10.1006/jmbi.2001.5154 RODRIGUEZ J, 1991, J CHEM PHYS, V94, P6020, DOI 10.1063/1.460439 RUPLEY JA, 1991, ADV PROTEIN CHEM, V41, P37 SCHEJTER A, 1964, BIOCHEMISTRY-US, V3, P1045, DOI 10.1021/bi00896a006 SCHEJTER A, 1984, BIOCHEMISTRY-US, V23, P1081, DOI 10.1021/bi00301a007 SHECHTER E, 1967, BIOPOLYMERS, V5, P788, DOI 10.1002/bip.1967.360050812 Smith JC, 2002, J MOL LIQ, V101, P27, DOI 10.1016/S0167-7322(02)00100-9 Stolow A, 2004, CHEM REV, V104, P1719, DOI 10.1021/cr020683w Stolow A, 2003, ANNU REV PHYS CHEM, V54, P89, DOI 10.1146/annurev.physchem.54.011002.103809 SUBRAMANIAN S, 1972, BIOPOLYMERS, V11, P1305, DOI 10.1002/bip.1972.360110614 SUTHERLAND JC, 1972, J CHEM PHYS, V57, P76, DOI 10.1063/1.1678020 TAKANO T, 1981, J MOL BIOL, V153, P95, DOI 10.1016/0022-2836(81)90529-5 TAKANO T, 1981, J MOL BIOL, V153, P79, DOI 10.1016/0022-2836(81)90528-3 TALER G, 1995, BIOCHEMISTRY-US, V34, P14209, DOI 10.1021/bi00043a027 TEETER MM, 1991, ANNU REV BIOPHYS BIO, V20, P577, DOI 10.1146/annurev.biophys.20.1.577 Vos MH, 1999, BBA-BIOENERGETICS, V1411, P1, DOI 10.1016/S0005-2728(99)00035-3 Wang W, 2000, J PHYS CHEM B, V104, P10789, DOI 10.1021/jp0008602 WEI YZ, 1994, J PHYS CHEM-US, V98, P6644, DOI 10.1021/j100077a034 Werner JH, 2006, P NATL ACAD SCI USA, V103, P11130, DOI 10.1073/pnas.0604712103 Wilson M. T, 1996, CYTOCHROME C MULTIDI, P611 Ye MP, 2007, BIOPHYS J, V93, P2756, DOI 10.1529/biophysj.107.106799 Ye S, 2007, AIP CONF PROC, V893, P1307, DOI 10.1063/1.2730382 Ye X, 2002, J AM CHEM SOC, V124, P5914, DOI 10.1021/ja017359n Ye XO, 2003, J PHYS CHEM A, V107, P8156, DOI 10.1021/jp0276799 Yeh SR, 1998, ACCOUNTS CHEM RES, V31, P727, DOI 10.1021/ar970084p Yokoyama K, 2001, J PHYS CHEM B, V105, P12622, DOI 10.1021/jp011217y Zang C, 2009, J AM CHEM SOC, V131, P2846, DOI 10.1021/ja8057293 Zelent B, 2004, J PHYS CHEM B, V108, P10317, DOI 10.1021/jp037664q Zhang LY, 2007, P NATL ACAD SCI USA, V104, P18461, DOI 10.1073/pnas.0707647104 Zhou HX, 2001, BIOPHYS CHEM, V93, P171, DOI 10.1016/S0301-4622(01)00219-8 Ye, Shuji Markelz, Andrea Ye, Shuji/B-4479-2010 Markelz, Andrea/0000-0003-0443-4319 NSFNational Science Foundation (NSF) [PHY-0349256, DBI-2959989]; University of Science and Technology of China; Fundamental Research Funds for the Central UniversitiesFundamental Research Funds for the Central Universities; National Natural Science Foundation of ChinaNational Natural Science Foundation of China (NSFC) [21073175]; National Basic Research Program of ChinaNational Basic Research Program of China [2010CB923300] This work was supported by NSF CAREER Grant PHY-0349256 and NSF MRI-R2 Grant DBI-2959989, the start-up funding from University of Science and Technology of China, the Fundamental Research Funds for the Central Universities, National Natural Science Foundation of China (Grant 21073175), and National Basic Research Program of China (Grant 2010CB923300). 3 2 20 Amer chemical soc Washington
Keywords: Chemistry; circular-dichroism; conformation change; dynamics; ferricytochrome-c; protein hydration; resolved resonance raman; spectroscopy; unfolded states; vibrational-relaxation; water-molecules